The potential of digitalization of resource regions of the Russian North - N. E. Egorov; G. S. Kovrov; S. V. Tishkov; A. D. Volkov (Модернизация, инновация, развитие, 2022)
Purpose: the study of the current state of the potential level of digitalization of the sectors of the economy of the northern regions of the resource type (NRRT) and to identify possible promising directions for their development.Methods: the research is based on the application of standard methods of data collection and processing, comparative analysis and rating assessment. The data of the Federal State Statistics Service and statistical collections of the Higher School of Economics for the period 2010–2020 were used.Results: the rating of the TOP 10 countries of the world on digital competitiveness is presented. A methodological approach is proposed to substantiate the attribution of NRRT subjects to the resource-type category by calculating the share of the statistical indicator "mining" in the structure of the gross regional product. An assessment of the resource dependence of the regions of the Far North was carried out, based on the analysis of which the criteria for assigning eight subjects of the Russian Federation to NRRT were determined. The analysis and assessment of the current state of the level of digitalization of NRRT, which showed the leading positions of the Magadan region, Yamalo-Nenets and Khanty-Mansi Autonomous Okrugs, was carried out. It is noted that the level of regional expenditures on the introduction and use of digital technologies does not significantly affect the composite integral index of the digitalization potential of the northern resource–type regions.Conclusions and Relevance: the development of methodology and research on digitalization of resource regions of the Russian North, the results of which are presented in this article, is being implemented in a number of areas: the development of a conceptual scheme and a system of indicators for monitoring the northern regions; the development and construction of a composite index of development of the digital economy in the regions of the North; the development of methodology for monitoring the development and use of "end-toend" digital technologies (technologies for working with big data); monitoring and assessment of the level of development of the digital economy in the Arctic municipalities; the study of the relationship between socio-economic and digital development of the regions of the Russian North; the development of digital technologies of regional and municipal management and the study of socio-economic effects of their implementation; the study of digital transformation of priority economic sectors of the northern regions.